Someone else's ears: Metacognitive auditory perspective taking in young and older adults - Chiara Valzolgher; Elena Gessa; Elena Giovanelli; Francesco Pavani (i-Perception)
Understanding others’ listening experiences is an instance of social metacognition. We investigate attributed listening experiences to fictional others in two online experiments involving two groups, young and older adults with normal hearing. We assessed the similarity between the judgement they gave for themselves and for two fictional characters (same or different age), with respect to listening experiences and effort required across various listening scenarios. In Exp. 1, all characters were described as having normal hearing; in Exp. 2, we introduced one additional older character with hearing loss. In both experiments, younger adults judged the older characters as experiencing more effort, irrespective of hearing loss. Instead, older adults reported to experience less effort than older characters, irrespective of characters’ hearing status and judged themselves closer to the young character. These findings show disparities in metacognitive auditory perspective taking in young and older adults, documenting a potential self-serving bias of older adults.